2019
DOI: 10.1140/epjc/s10052-019-6978-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolating the confining color field in the SU(3) flux tube

Abstract: We extend a previous numerical study of SU(3) Yang-Mills theory in which we measured the spatial distribution of all components of the color fields surrounding a static quark-antiquark pair for a wide range of quarkantiquark separations, and provided evidence that the simulated gauge invariant chromoelectric field can be separated into a Coulomb-like 'perturbative' field and a 'nonperturbative' field, identified as the confining part of the SU(3) flux tube field.In this paper we hypothesize that the fluctuat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 56 publications
(96 reference statements)
3
48
0
Order By: Relevance
“…While such flux tubes have been studied for the ordinary static potential using lattice gauge theory for quite some time (see refs. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]), this is a rather new direction for hybrid static potentials, where first results appeared only recently [49][50][51][52]. In this paper we substantially extend existing work by performing computations for seven hybrid static potential sectors characterized by quantum numbers Λ ( )…”
Section: Introductionmentioning
confidence: 92%
“…While such flux tubes have been studied for the ordinary static potential using lattice gauge theory for quite some time (see refs. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]), this is a rather new direction for hybrid static potentials, where first results appeared only recently [49][50][51][52]. In this paper we substantially extend existing work by performing computations for seven hybrid static potential sectors characterized by quantum numbers Λ ( )…”
Section: Introductionmentioning
confidence: 92%
“…Recent times have witnessed an increasing numerical effort toward a more comprehensive numerical description of the color field around static sources, via the measurement of all components of both chromoelectric and chromomagnetic fields on all transverse planes passing through the line between the quarks [38]; of the spatial distribution of the stress energy-momentum tensor [39,40]; and the flux densities for hybrid static potentials [41,42]. A more complete numerical description of the color field around the sources brings improved visualization, enabling us to grasp features otherwise less visible.…”
Section: Introductionmentioning
confidence: 99%
“…In the numerical study [38] we simulated the spatial distribution in three dimensions of all components of the chromoelectric and chromomagnetic fields generated by a static quark-antiquark pair in pure SU(3) lattice gauge theory. We found that, although the components of the simulated chromoelectric field transverse to the line connecting the pair are smaller than the simulated longitudinal chromoelectric field, these transverse components are large enough to be fit to a Coulomb-like 'perturbative' field produced by two static sources parameterized by effective charges ±Q of the sources (see Eq.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is associated with not only a linearly rising potential but also the formation of a flux tube (see Refs. [21,22] and references therein) with transverse collective modes [23,24]. This is a physical object on its own, which is well beyond the language of Green's functions and the usual Feynman diagrams.…”
Section: Introductionmentioning
confidence: 99%